PENGARUH PERTIMBANGAN PENERIMAAN KLIEN TERHADAP REPUTASI KANTOR AKUNTAN PUBLIK (Survai pada Kantor Akuntan Publik anggota Forum Akuntan Pasar Modal) - Mutia, Keukeu (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2015)
The public accountant profession was a profession which had public’s trust in the field of financial report audit. A financial report which had been audited by a public accountant would be used by those who got interests in the decision making. Based on those facts, the writer felt interested in doing a study on 45 public accounting firm members of FAPM in Indonesia. Referring to those thoughts in this thesis, the hypothesis of this study were: (1) engagement risk and professional fee affected the public accounting firm reputation simultaneously; (2) engagement risk affected the public accounting firm reputation; (3) professional fee affected the public accounting firm reputation; and (4) independency affected the public accounting firm reputation. The type of the study was causal corelational by using survey method and prime data collection trough questioners using likert scale. Sampling was using random stratified method and data analysis was using path analysis model. Hypothesis test result showed that (1) correlation of engagement risk and professional fee simultaneously had affection to public accounting firm reputation; (2) engagement risk had affection to public accounting firm reputation; (3) professional fee had affection to accounting public firm reputation; and (4) independency had affection to public accounting firm reputation.